Validity and Reliability of the Turkish Nursing Students’ Self-Perceptions about Safe Medication Management - Şimşekli, Derya; Koyunoğlu, Bedriye Cansu; Karabulutlu, Elanur Yilmaz (Makara Journal of Health Research, 2026)
Background: Safe medication management is central to nursing education and patient safety. To the best of our knowledge, there is currently no validated Turkish instrument specifically designed to assess nursing students’ self-perceptions regarding safe medication management. This study aimed to evaluate the validity and reliability of the Turkish version of the Nursing Students’ Self-Perceptions about Safe Medication Management (NURSPeM). Methods: This methodological study was conducted at a single university using convenience sampling. Data were collected from a sample of 400 nursing students using the NURSPeM. Construct validity was examined with confirmatory factor analysis (CFA). Internal consistency was evaluated using Cronbach’s alpha, and test–retest reliability using intraclass correlation coefficients (ICCs). Results: Questionnaire 1 showed adequate fit (CMIN/df = 1.67, RMSEA = 0.041, CFI = 0.912). Questionnaire 2 demonstrated acceptable fit (CMIN/df = 3.02, RMSEA = 0.071, CFI = 0.905). The Cronbach alpha values ranged from 0.815 to 0.918, and ICC from 0.854 to 0.930. Conclusions: The Turkish NURSPeM is a valid and reliable tool for assessing nursing students’ self-perceptions of safe medication management in nursing education.